Prodromus of a fern flora for Bolivia. XXXV. Dryopteridaceae - Kessler, Michael; Moran, Robbin C.; Mickel, John T.; Matos, Fernando B.; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis of the 207 species of Dryopteridaceae in 15 genera currently known from Bolivia. This is the secondmost species-rich fern family in the country and includes the most diverse genus (Elaphoglossum with 127 species). No fewer than 32 species of Dryopteridaceae are endemic to Bolivia. Elaphoglossum catenatum, a new species from the Bolivian Yungas, is here described and illustrated. We also provide a new combination for Acrostichum papyraceum in Elaphoglossum and designate a lectotype for Elaphoglossum ambiguum. Illustrations for all Bolivian taxa of Elaphoglossum are provided. Taxonomic problems remain in a number of genera, especially Elaphoglossum, Megalastrum, and Polystichum.